Strength and Power Assessment - Wilson, G.
Reprint with the permission of Blackwell science Asia from Bloomfield, Ackland & Elliott, Applied Anatomy and Biomechanics in Sport There are a variety of reasons why the coach or sport scientist would want to accurately assess the muscular strength and power of an athlete. These include: - Establishing the relevance of strength and power to a particular sport - Determining the strengths and weaknesses of an athlete by comparing test performances with group norms. By profiling the athlete in this manner, the test results can be used for the implementation of specific resistance training regimens - Monitoring training progress or the progress of injury rehabilitation.